1992
DOI: 10.1042/bj2830055
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylethanolamine metabolism in rat liver after partial hepatectomy. Control of biosynthesis of phosphatidylethanolamine by the availability of ethanolamine

Abstract: The effect of partial (70%) hepatectomy on phosphatidylethanolamine (PE) synthesis was studied in rat liver during the first 4 post-operative days. Between 4 and 96 h after partial hepatectomy, the mass of PE increased from 30% to 80% of sham-operation values. In line with the increase in PE mass, the rate of PE synthesis in vivo from [14C]ethanolamine was stimulated 1.6- and 1.3-fold at 22 and 48 h after partial hepatectomy respectively. Surprisingly, the activity of CTP:phosphoethanolamine cytidylyltransfera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 53 publications
2
32
0
Order By: Relevance
“…In this pathway, both the availability of Etn and 1,2-diacylglycerol and the activity of enzymes, choline (ethanolamine) kinase and CTP:phosphoethanolamine cytidylyltransferase, are required (11). Among these, the supply of Etn seems to primarily inf luence PtdEtn synthesis in hepatocytes (12). PtdEtn can also be synthesized by the decarboxylation of phosphatidylserine (13) and by a base-exchange reaction (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this pathway, both the availability of Etn and 1,2-diacylglycerol and the activity of enzymes, choline (ethanolamine) kinase and CTP:phosphoethanolamine cytidylyltransferase, are required (11). Among these, the supply of Etn seems to primarily inf luence PtdEtn synthesis in hepatocytes (12). PtdEtn can also be synthesized by the decarboxylation of phosphatidylserine (13) and by a base-exchange reaction (14).…”
Section: Discussionmentioning
confidence: 99%
“…PtdEtn can also be synthesized by the decarboxylation of phosphatidylserine (13) and by a base-exchange reaction (14). These pathways, however, are not the major routes of PtdEtn synthesis in hepatocytes (9,12,14).…”
Section: Discussionmentioning
confidence: 99%
“…Pulse-label studies demonstrated that exposure of freshly isolated hepatocytes to increasing concentrations of ethanolamine resulted in an enhanced incorporation of labelled glycerol and ethanolamine into PtdEtn. The enhanced PtdEtn synthesis was accompanied by a considerable increase in the pool size of phosphoethanolamine, whereas the amount of CDPethanolamine remained constant [13,14]. Furthermore, exposure of hepatocytes to phorbol ester has been shown to stimulate PtdEtn synthesis, to enhance the activity of ECT and to reduce phosphoethanolamine and CDPethanolamine pool sizes [37].…”
Section: Discussionmentioning
confidence: 99%
“…The ratecontrolling role of ECT is partially determined on the basis of experiments with freshly isolated hepatocytes. Sundler and Åkesson [13] and Houweling et al [14] reported that, at physiological extracellular ethanolamine concentrations, phosphoethanolamine starts to accumulate with the level of CDPethanolamine remaining constant, implicating that ECT has become rate-limiting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation